IMPROVING READING COMPREHENSION OF GRADE X STUDENTS AT SMK NEGERI 1 DAMPAL SELATAN TOLITOLI THROUGH DRTA (DIRECTED READING THINKING ACTIVITY) - Nurherika, Nurherika; M. Said, Mawardin; Patmasari, Andi; Marhum, Mochtar (e-Journal of ELTS (English Language Teaching Society), 2025)
The objective of this research is to find out whether the use of DRTA (Directed Reading Thinking Activity) strategy can improve the reading comprehension of class X students of SMK Negeri 1 Dampal Selatan or not. This research used a pre-experimental design that involved only one class as the experimental class. The sample of this research was class X TKJ with 31 students as the experimental class selected by using purposive sampling technique. The instruments of data collection were tests, they were pretest and posttest. The experimental class was given treatment by using the DRTA (Directed Reading Thinking Activity) strategy. The data were analyzed statistically to measure the difference in score. The results shows an increase between the pretest and posttest results. The students means score before given the treatment was 51.10. After the treatment, the means score of students in the posttest was 71.48. By applying a significant level of 0.05, the researchers found that the value of t-counted (5.31) was higher than the t table (1.697). Based on these results, it can be concluded that the DRTA (Directed Reading Thinking Activity) strategy is effective to improve reading comprehension of grade X students at SMK Negeri 1 Dampal Selatan and it can be applied by teachers in teaching and learning process.